KOMITMEN ORGANISASI DITINJAU DARI MASA KERJA - Khairuddin, Khairuddin (Granada El-Fath, 2021)
This study aims to empirically determine the description of organizational commitment. The sampling technique was carried out by total sampling technique and got 43 samples. The research instrument used was the organizational commitment scale. This type of research is quantitative research with descriptive and comparative models. The data analysis technique used is the one sample t-test. Researcher hypothesized that teachers with longer period of work will tend to have higher organizational commitment. The results showed that the organizational commitment of the teachers was generally high. In accordance with the proposed hypothesis, it is said that there is a difference in organizational commitment between teachers who have worked for more than 5 years and teachers who have worked for less than 5 years. The t-test results obtained were p = 0.006 (p